Combined Waste Assessment Model and Fuzzy-FMEA in Lean Six Sigma for Generating Waste Reduction Strategy: A Proposed Model - Basuki, Demas Emirbuwono; Cahyo, Winda Nur; Handayani, Dwi; Apriani, Ratna Agil; Mukarim, Rifki Nurul (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2023)
Lean Six Sigma is a method that is quite effective in solving waste problems in the production process, but it is often not optimal because of the tools used in the DMAIC process. Therefore, we developed a proposed model by combining the Waste Assessment Model and Fuzzy-FMEA in Lean Six Sigma to reduce waste in the production process. The Waste Assessment Model was used at the defined stage to identify waste, while the Fuzzy-FMEA was used for priority waste risk analysis at the analysis stage. Based on the results of the Waste Assessment Model case study, defects were the most influential waste, with a percentage of 22.38%. At the analysis stage using Pareto diagrams, tearing was the dominant defect in the Nike Extreme. Based on calculations using the Fuzzy-FMEA method, the highest cause of defects was errors in processes or missed processes that caused the failure. Improvement was carried out at the improvement stage, and we found it necessary to carry out intensive and periodic control or supervision of the Nike Extreme production process. Based on these results, the proposed Lean Six Sigma model can be used to identify and reduce waste in the production process.